СПОСОБИ ПІДВИЩЕННЯ ККД І ПОКРАЩЕННЯ ОСНОВНИХ ХАРАКТЕРИСТИК DC/DC ПЕРЕТВОРЮВАЧІВ ІЗ ПОЗДОВЖНІМ КЛЮЧЕМ - Волков, І.В.; Голубєв, В.В.; Зозульов, В.І. (Інститут електродинаміки Національної академії наук України, 2020)
The results of the study of three new variants of DC/DC-pulse converters (DСС) with a longitudinal transistor switch are presented. It is established that the creation of conditions in which there is no sharp break of the DCС input current, leads to a smooth change in voltage on its switch and to minimize the range of variation of this voltage, which is accompanied by reduced power losses on the switch and improved power quality at the DCС input and output. It is shown that the creation of such conditions is implemented using two-winding chokes and an input buffer node. Exact and approximate analytical expressions are presented that describe the processes in such converters, which are in good agreement with the results of computer simulation. The most acceptable ways to control the switches of DCС-1...DCС-3 were found out. Recommendations for the use of DCС -1... DCС-3 are given. Ref. 11, Fig. 11, table.